Effects of Mn‐Doping on the Structural and Electrochemical Properties of Na3Ni2SbO6 for Sodium‐Ion Battery. Issue 5 (14th January 2020) - Kee, Yongho; Put, Brecht; Dimov, Nikolay; Staykov, Aleksandar; Okada, Shigeto
Abstract: Recently, layered O′3‐Na3 Ni2 SbO6 has been investigated as a unique cathode material for Na‐ion batteries due to the good electrochemical performance via O′3‐P′3 phase transitions in the voltage range between 2.0 and 4.0 V vs Na + /Na. However, at present it is not well understood whether transition metal doping of the pristine structure could improve the phase transition kinetics during charge/discharge. In this study, we synthesized Mn‐doped Na3 Ni2‐x Mnx SbO6 ( x =0, 0.25, 0.5) layered oxides and investigated their feasibility as cathode materials for Na‐ion batteries using ex‐situ X‐ray diffraction (XRD) coupled with DFT calculations. The results show that light Mn doping ( x =0.25) energetically enhances the O′3‐P′3 phase transition kinetics with smaller unit‐cell‐volume changes. However, the heavily doped ( x =0.5) sample suffers from large polarization, which could be attributable to the reduced two‐phase reaction range and a large unit‐cell‐volume change upon sodium extraction. Abstract : A pinch of Mn : Light Mn doping ( x =0.25) on Na3 Ni2‐ x Mn x SbO6 is beneficial for O′3‐P′3 phase transition kinetics, while heavy Mn doping ( x =0.5) energetically reduces the two‐phase reaction range and brings a large unit cell volume change upon sodium extraction.